2012
DOI: 10.1002/ijc.27470
|View full text |Cite
|
Sign up to set email alerts
|

Prospectively measured thyroid hormones and thyroid peroxidase antibodies in relation to breast cancer risk

Abstract: Thyroid hormones influence both normal breast cell differentiation and breast cancer cell proliferation and stimulate the angiogenesis of certain cancer forms. Several cross-sectional studies have measured thyroid hormones/autoantibodies in breast cancer ceases vs. controls, but it is difficult to determine the cause-effect direction in these studies. Only three prospective studies have reported on the subject so far. The aim of our study was to investigate prediagnostically measured levels of thyroid hormones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 45 publications
6
82
1
3
Order By: Relevance
“…Most of the previous studies examined the effect of thyroid hormone levels on breast cancer risk in a case-control setting (14,16,17,29), in which reverse causation may be difficult to rule out. Our findings are in line with three of the earlier cohort studies that found an association between higher premorbid levels of thyroid hormone and breast cancer risk (11,12,15), while the fourth cohort study found an association between low levels of free thyroxine and an increased risk of breast cancer (9). The lack of increase in the risk of breast cancer in women with hypothyroidism, observed in this study, is also in agreement with the results of a recent meta-analysis of 12 observational studies showing no association between hypothyroidism and breast cancer risk (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Most of the previous studies examined the effect of thyroid hormone levels on breast cancer risk in a case-control setting (14,16,17,29), in which reverse causation may be difficult to rule out. Our findings are in line with three of the earlier cohort studies that found an association between higher premorbid levels of thyroid hormone and breast cancer risk (11,12,15), while the fourth cohort study found an association between low levels of free thyroxine and an increased risk of breast cancer (9). The lack of increase in the risk of breast cancer in women with hypothyroidism, observed in this study, is also in agreement with the results of a recent meta-analysis of 12 observational studies showing no association between hypothyroidism and breast cancer risk (18).…”
Section: Discussionsupporting
confidence: 93%
“…Some epidemiological studies have reported increased risks associated with hypothyroidism (8,9), hyperthyroidism (10,11,12), goiter (13) and thyroid autoimmune diseases (14,15), while others have found no association (9,16,17,18). Only four studies employed a cohort design (9,11,12,15); in case-control studies, reverse causation is a plausible competing explanation since breast cancer or its treatment may affect thyroid hormone levels (19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that there is an association between breast cancer and thyroid cancer; this association may be attributable to common etiologic features, pathologic processes, or treatment-related factors (27,28) that these 2 cancers share. Previous studies suggested the relationship between serum levels of thyroid hormones or thyroid peroxidase autoantibodies and the risk or prognosis of breast cancer (29)(30)(31)(32). Radioiodine therapy is the main postoperative treatment for patients with differentiated thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This issue needs clarification with further research both pathophysiologically and clinically. Most of these studies have commonly emphasized the necessity of screening for breast cancer in patients with thyroid disorders [13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%